2017
DOI: 10.1128/aac.01220-16
|View full text |Cite
|
Sign up to set email alerts
|

Caged Garcinia Xanthones, a Novel Chemical Scaffold with Potent Antimalarial Activity

Abstract: Caged Garcinia xanthones (CGXs) constitute a family of natural products that are produced by tropical/subtropical trees of the genus Garcinia. CGXs have a unique chemical architecture, defined by the presence of a caged scaffold at the C ring of a xanthone moiety, and exhibit a broad range of biological activities. Here we show that synthetic CGXs exhibit antimalarial activity against Plasmodium falciparum, the causative parasite of human malaria, at the intraerythrocytic stages. Their activity can be substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
(82 reference statements)
1
20
0
Order By: Relevance
“…This suggests a different mechanism of action from other anti-malarial drugs, such as atovaquone, that target parasite mitochondria. The cytotoxicity of the compounds against HEK293 cells was in the µM range, making them selectively toxic to the parasite at the active concentration (SI > 100) [230]. A tetrahydroxanthone dimer, dicerandrol D ( 370 ), from the endophytic fungus Diaporthe sp.…”
Section: Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a different mechanism of action from other anti-malarial drugs, such as atovaquone, that target parasite mitochondria. The cytotoxicity of the compounds against HEK293 cells was in the µM range, making them selectively toxic to the parasite at the active concentration (SI > 100) [230]. A tetrahydroxanthone dimer, dicerandrol D ( 370 ), from the endophytic fungus Diaporthe sp.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Natural products have also modulated their parasite killing effect by disrupting the haem detoxification systems as well as induction of oxidative stress and lipid peroxidation in the parasite (Table 1). Some natural products have also been reported to mediate antiplasmodial activity by inducing morphological and ultrastructural changes that are detrimental to parasite viability [230, 289].…”
Section: Mechanism Of Action Of Antiplasmodial Natural Products: Plasmentioning
confidence: 99%
“…Xanthones are a class of oxygen-containing heterocycles with γ-pyran moiety condensed with two benzene rings, which are widely distributed in nature. 18) In recent years, xanthone derivatives have been received considerable attention in the field of medicinal chemistry because of their diversely biological functions, 20,21) such as anti-oxidant, 22) anti-hypertensive, 23) anti-convulsant, 24) anti-cholinesterase, 25) anti-malarial, 26) antimicrobial, 27) anti-inflammatory, 28) and anti-cancer activities. 29) Besides, they also served as the effective inhibitors of several enzymes like α-glycosidase, 30,31) topoisomerase, 32) proteinkinase, 33) aromatase.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic Caged Garcinia xanthones (CGXs) exhibit anti-malarial activity against P. falciparum with low toxicity. It was reported that CGXs treatment affect malaria parasites relating to morphological changes, signi cant reduction of parasitemia (the percentage of infected red blood cells), and aberrant mitochondrial fragmentation [21]. Benzophenone (isoxanthochymol) was isolated from the roots of G. polyantha which showed strong chemosuppressive activity of parasitic growth found in P. falciparum [22].…”
Section: Discussionmentioning
confidence: 99%